Optimalisasi Biaya Transportasi Distribusi Bahan Baku Kopi dengan Menggunakan Metode Vogel's Approximation dan Perangkat Lunak QM for Windows di PT. CFT - bustommy, Abby yazid; Angga Widyaswara; Muhammad Ikhsanudin basri (Universitas Tangerang Raya, 2024)
The distribution process of coffee raw materials at PT CFT Lampung requires large transportation costs. The problem is the limited warehouse capacity and different shipping destinations. The research aims to minimize transportation costs in distributing coffee raw materials from PT CFT in Lampung to various factories in the Greater Jakarta area. VAM is an algorithm used to find the minimum cost in transportation problems. The transportation problem finds that total demand and total supply do not match, requiring a dummy column to help with optimal allocation. This research successfully minimized the transportation cost of coffee raw materials from PT CFT in Lampung to various factories in Jabodetabek using Vogel's Approximation Method (VAM) and QM for Windows software, with a total cost of IDR 66,560,000.